"And Breathes a Spirit Through the Finish'd Whole": Empiricism, Poetry and Devotion in Anna Letitia Barbauld's Poetic Epistemology. Issue 6 (2nd November 2022) - Schurch, Millie
ABSTRACT: Anna Barbauld creates a poetic epistemology, a particular way of knowing, that she uses to shape her readers' encounters with her poems. She demonstrates that poetry can transform empirical observation into a devotional experience that the reader can take forward beyond their immediate encounter with the poem. She combines observations with poetic techniques—and notably with epistolary characteristics—to produce an epistemology that draws on, questions, and reconfigures an empirical model, paying particular attention to the gendering of different modes and methods of knowledge production and their potential for religious devotional experience. Barbauld's poetic epistemology also, significantly, positions the reader as a participant, accomplice or critic in the act of creating knowledge at the moment of reading. She aims to instill in the reader a new, transformational, responsive mode of observation and interpretation that will imbue their future experiences of poetry, of God's creation, and the process of knowledge production itself with poetic and devotional ways of knowing.